2005
DOI: 10.1111/j.1447-0756.2005.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Microwave endometrial ablation for menorrhagia caused by large submucous myomas

Abstract: Microwave endometrial ablation improves menorrhagia caused by large submucous myomas when the microwave applicator reaches all parts of the uterine cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 10 publications
0
25
0
3
Order By: Relevance
“…Since Kanaoka et al reported for the first time in 2005 that microwave endometrial ablation improves menorrhagia caused by large submucous fibroids [10], other scholars have researched this technique. Zhang et al reported that PMWA for fibroids was feasible and safe, with a fibroid regression rate of 78.7% and 93.1% at 6 and 12 months after ablation, respectively, and there were no serious adverse events in any patient after the treatment [5].…”
Section: Discussionmentioning
confidence: 99%
“…Since Kanaoka et al reported for the first time in 2005 that microwave endometrial ablation improves menorrhagia caused by large submucous fibroids [10], other scholars have researched this technique. Zhang et al reported that PMWA for fibroids was feasible and safe, with a fibroid regression rate of 78.7% and 93.1% at 6 and 12 months after ablation, respectively, and there were no serious adverse events in any patient after the treatment [5].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, PMC has been mainly used in the treatment of hepatic tumors and myomas in the uterus, and it was recognized as an effective therapy for these two types of tumors (14)(15)(16)(17)(18)(19)(20). To our knowledge, ultrasonography (US)-guided PMC in the treatment of breast cancer has not been reported.…”
Section: Patient Enrollmentmentioning
confidence: 90%
“…Kanaoka et al ont traité trois patientes ne souhaitant pas d'hystérectomie et présentant de larges fibromes supé-rieurs à 3 cm par micro-ondes. Il a obtenu une aménorrhée chez chacune d'entre elles [35]. Soysal et al ont proposé de traiter les fibromes sous-muqueux de 93 patientes par résection endométriale ou thermocoagulation seule dans une étude prospective randomisée (patientes de plus de 40 ans avec un utérus de taille inférieure à 12 semaines de grossesse) avec la même efficacité dans les deux groupes [36].…”
Section: Endométrectomieunclassified